Effect of ghrelin and its analogues, BIM‐28131 and BIM‐28125, on the expression of myostatin in a rat heart failure model. Issue 1 (18th September 2012) - Lenk, Karsten; Palus, Sandra; Schur, Robert; Datta, Rakesh; Dong, Jesse; Culler, Michael D.; Anker, Stefan; Springer, Jochen; Schuler, Gerhard; Adams, Volker
Abstract : Background: In chronic heart failure (CHF), cachexia is a hallmark of the terminal stage of this disease and is associated with a severely reduced quality of life and poor prognosis. Therapeutic options are currently not available. Ghrelin and its analogues BIM‐28125 and BIM‐28131 (now known as RM‐131) have been shown to increase weight in a rat model of CHF. It has been further demonstrated that the expression of myostatin, a negative regulator of skeletal muscle mass, is increased in CHF. The aim of the study was to investigate the influence of ghrelin or its analogues on myostatin in CHF. Methods: In an animal model of CHF, Sprague–Dawley rats received either ghrelin or two ghrelin analogues BIM‐28125 and BIM‐28131 in two different concentrations (50 and 500 nmol/kg/day) compared to placebo. The compounds were delivered using osmotic mini pumps. The expression of myostatin was analyzed in skeletal muscle by RT‐PCR and Western blot, and muscle mass of gastrocnemius muscle was measured. The plasma levels of tumor necrosis factor alpha (TNF‐α) were measured. Results: The relative weight of the gastrocnemius muscle of the sham‐operated group was significantly increased compared to placebo‐treated CHF rats. The application of ghrelin analogue BIM‐28125 and BIM‐28131 in their higher concentrations led to a significant reduction in myostatin mRNA expression in comparison to placebo. Myostatin protein expression was significantly reduced in both concentrations of ghrelin and BIM‐28131 and in the lower concentration of BIM‐28125. The increase of TNF‐α plasma concentration in the CHF‐animals could be abolished by all used substances. Conclusions: In an animal model of CHF, the expression of myostatin is significantly reduced in the skeletal muscle after application of ghrelin and most concentrations of its analogues BIM‐28125 and BIM‐28131 possibly due to anti‐inflammatory effects.